PENGARUH QUICK RATIO (QR), DEBT TO ASSET RATIO (DAR), DAN RETURN ON EQUITY (ROE) TERHADAP HARGA SAHAM PADA LQ45 TAHUN 2020-2022 - Nur Lailatun Nikmah, Devi Agustin; Yudiantoro, Deny (Program Studi Manajemen Fakultas Ekonomi UST, 2024)
This research aims to determine the influence of the Quick Ratio, Debt to Asset Ratio, and Return On Equity on stock price indexes at LQ 45 in 2020-2022. This research is in the form of quantitative research with an associative type that examines the relationship between variables and the object under study which have cause and effect. The objects studied are companies registered in LQ 45 during the 2020-2022 period which also publish annual reports. The number of samples used was 25 companies determined by purposive sampling. Using panel data regression analysis with the help of the E Views 9 application. The results of the research are a) Quick ratio has no effect on prices even though LQ 45, b) Debt To Asset Ratio has no positive effect on stock prices, c) Return On Equity has a positive effect and significant to changes in share prices, d) QR. DAR and ROE simultaneously have a significant effect on changes in share prices on the LQ 45 index.